MAP decoding of linear block codes based on a sectionalized trellis of the dual code - Schreier, Peter J.; Costello, Jr., Daniel J. (Proc.\ Int.\ Zurich Seminar Broadband Comm.)
Block codes for use in turbo coding schemes provide an alternative to punctured convolutional codes when high rate component codes are needed. Since block codes have large, time-varying trellis diagrams, full maximum a posteriori (MAP) soft-in soft-out decoders are very complex. It is shown how to modify the MAP algorithm to utilize a sectionalized trellis diagram of the dual code for decoding, which minimizes computational complexity for high rate component codes. This paper also gives simulation results for some high rate block turbo codes

Short-time estimates for heat kernels associated with root systems - Rösler, Margit (Special Functions (HongKong 1999))

Von der Notwendigkeit der Erziehungswissenschaft: Begründungsversuche und Reflexion
Keywords: Erziehungswissenschaft; Pädagogik

Time-Resolved Recording of Ionic Dyestuff Aggregation by Static Light Scattering - Inglés, Sergio Escudero; Katzenstein, Armin; Schlenker, Wolfgang; Huber, Klaus (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Galois Group Computation for Rational Polynomials - Geissler, Katharina; Klüners, Jürgen (Journal of Symbolic Computation)
We describe methods for the computation of Galois groups of univariate polynomials over the rationals which we have implemented up to degree 15. These methods are based on Stauduhar’s algorithm. All computations are done in unramified p -adic extensions. For imprimitive groups we give an improvement using subfields. In the primitive case we use known subgroups of the Galois group together with a combination of Stauduhar’s method and the absolute resolvent method.
Keywords: Computational Mathematics; Algebra and Number Theory

Computing Local Artin Maps, and Solvability of Norm Equations - Acciaro, Vincenzo; Klüners, Jürgen (Journal of Symbolic Computation)
Let L = K(α) be an Abelian extension of degree n of a number field K, given by the minimal polynomial of α over K. We describe an algorithm for computing the local Artin map associated with the extension L / K at a finite or infinite prime v of K. We apply this algorithm to decide if a nonzero a ∈ K is a norm from L, assuming that L / K is cyclic.
Keywords: Computational Mathematics; Algebra and Number Theory

Explicit Galois Realization of Transitive Groups of Degree up to 15 - Klüners, Jürgen; Malle, Gunter (Journal of Symbolic Computation)
We describe methods for the construction of polynomials with certain types of Galois groups. As an application we deduce that all transitive groups G up to degree 15 occur as Galois groups of regular extensions of ℚ (t), and in each case compute a polynomial f ∈ ℚ [ x ] with Gal(f) = G.
Keywords: Computational Mathematics; Algebra and Number Theory

A Polynomial with Galois GroupSL2(11) - Klüners, Jürgen (Journal of Symbolic Computation)
We compute a polynomial with Galois group SL₂(11) over ℚ. Furthermore we prove that SL₂(11) is the Galois group of a regular extension of ℚ (t).
Keywords: Computational Mathematics; Algebra and Number Theory

Nonaqueous Synthesis of Mesostructured Aluminophosphate/Surfactant Composites: Synthesis, Characterization, and In-Situ SAXS Studies - Tiemann, Michael; Fröba, M.; Rapp, G.; Funari, S. S. (Chemistry of Materials)
Mesostructured aluminophosphate/dodecyl phosphate composite materials were synthesized under aqueous and alcoholic conditions. The syntheses were monitored by temperature- and time-resolved in-situ small-angle X-ray scattering (SAXS). In the aqueous synthesis, a lamellar mesostructure is formed within the first few minutes of the reaction; this structure maintains a constant d spacing independent of the reaction time and temperature. The alcoholic synthesis at low temperature yields a mixture of a lamellar and a supposedly inverted hexagonal mesostructure. SAXS investigations show that these two phases evolve competitively. The lamellar structure is favored by higher temperatures and/or longer synthesis times; above ∼70 °C it is formed exclusively. Mixtures of both phases can be isolated as solid materials, but thermal analysis shows that the inverted hexagonal product transforms into the lamellar phase at ∼35−43 °C. The alcoholic synthesis is a highly cooperative reaction; the pure surfactant/alcohol systems are not lyotropic as long as the inorganic reactants are absent. In comparison, the surfactant/water system with the same surfactant concentrations as employed for the aqueous syntheses is lyotropic with a lamellar structure.

NMR Characterization of Mesostructured Aluminophosphates - Schulz, M.; Tiemann, Michael; Fröba, M.; Jäger, C. (The Journal of Physical Chemistry B)
The atomic structure of ordered mesostructured aluminophosphates with dodecyl phosphate as the structure-directing template was investigated by multinuclear solid-state NMR. Two different types of materials were studied:  one with the template headgroup as the only phosphate source and one where additionally phosphoric acid was used in the synthesis. All 31P and 27Al NMR resonances can be subdivided into three groups depending on the sample composition. Furthermore, 2D heteronuclear correlation NMR measurements allow a conclusive and unambiguous identification of the phosphate headgroup resonances of the template molecules and the determination of water and/or hydroxyl units. Most notably, there is an obvious correlation between the d001 values of the samples as measured by powder X-ray diffraction and the appearance of the various groups of 27Al and 31P resonances.

In-situ small angle x-ray scattering (SAXS) studies on the formation of mesostructured aluminophosphate / surfactant composite materials - Tiemann, Michael; Fröba, M.; Rapp, G.; Funari, S.S. (Nanoporous Materials II, Proceedings of the 2nd Conference on Access in Nanoporous Materials)
Mesostructured aluminophosphate / surfactant composite materials were prepared from aqueous and alcoholic systems. Syntheses in ethanol or methanol, respectively, lead to mixtures of two nanostructured phases. One of these consists of hexagonally arranged rod-like assemblies of the surfactant molecules with the head groups located in the centres, encapsulating the inorganic aluminophosphate; the other is lamellar. The syntheses were monitored by in-situ temperature- and time-resolved small angle X-ray scattering (SAXS).

Nonlinear Polariton Pulse Propagation in Bulk Semiconductors - Meier, Torsten; Förstner, J.; Knorr, A.; Kuckenburg, S.; Koch, S.W.; Giessen, H.; Linden, S.; Kuhl, J. (physica status solidi (b))
Nonlinear propagation of optical pulses through an extended bulk semiconductor is investigated using the coupled semiconductor Maxwell-Bloch equations including excitation induced correlations. For short pulse excitation around the exciton resonance, the theory describes the development of polariton beats and their suppression at increasing input pulse intensities due to the coupling of single exciton states to the Coulomb-correlated continuum of two-exciton states. A comparison of the theoretical results with experimental observations for CdSe bulk material is presented.

Analysis of Excitonic Absorption Changes Induced by Incoherent Exciton and Electron-Hole-Pair Populations - Meier, Torsten; Koch, S.W. (physica status solidi (b))
The density-dependent absorption in the presence of incoherent occupations of excitons and electron–hole pairs is analyzed including many-body correlations represented by exciton to two-exciton transitions. At low temperatures the exciton resonance is bleached and shifts to higher energies with increasing density. For higher temperature, the blue shift disappears and pure bleaching is obtained.

Helmut Obst: Apostel und Propheten der Neuzeit. Gründer christlicher Religionsgemeinschaften des 19. und 20. Jahrhunderts, Göttingen 2000 - Schroeter-Wittke, Harald (http://www.amazon.de)

Frank Hiddemann / Jürgen Reifarth (Hg.): Öffentlich Predigten. Prominente Predigten aus dem Thüringer Kanzelstreit, Gütersloh 2000 - Schroeter-Wittke, Harald (http://www.amazon.de)

"Wer hören will, muß fühlen." Musikalische Seelsorge als Kunst der Umordnung - Schroeter-Wittke, Harald (Pastoraltheologie)

Bernhard Grom: Religionspädagogische Psychologie des Kleinkind-, Schul- und Jugendalters, Düsseldorf 2000 - Schroeter-Wittke, Harald (http://www.amazon.de)

Erlebnis Spiritualität - Schroeter-Wittke, Harald (meditation)

Coherent Control of Absorption and Free Polarization Decay in GaAs Quantum Wells: Time and Spectral Domain Studies - Meier, Torsten; Yee, D.S.; Yee, K.J.; Hohng, S.C.; Kim, D.S.; Koch, S.W. (Physical review letters)
Two phase-locked pulses are used to coherently excite excitonic polarizations. It is shown that the second pulse can either be strongly amplified by taking up energy gained from the destruction of the exciton polarization or can be decreased drastically by giving up all its energy to excitons. Both the temporal and the spectral signatures of the transmitted pulse shapes agree well with model calculations.

χ(5)-signatures in the optical Stark effect - Meier, Torsten; Brick, P.; Ell, C.; Khitrova, G.; Gibbs, H.M.; Koch, S.W. (Quantum Electronics and Laser Science Conference (QELS 2000))

Semiclassical Effective Hamiltonian For Coupled Electronic And Nuclear Optical Response - Meier, Torsten; Chernyak, V.; Tretiak, S.; Tsiper, EV..; Mukamel, S. (Condensed Matter Theories)

Die Dialektik der Globalisierung in Technik, Ökonomie, Politik und Kultur (The Dialectic of Globalization in Technology, Economy, Polity, and Culture) - Fuchs, Christian; Hofkirchner, Wolfgang (Online-Proceedings Jubiläumskongresses der Österreichischen Gesellschaft für Soziologie)

Nanometer Scale Lateral Structures of MOS Type Layers - Hilleringmann, Ulrich; Vieregge, T; Horstmann, JT (Proceedings Micro. tec)

Coherent dynamics of photoexcited semiconductor superlattices in homogeneous electric fields - Meier, Torsten; Kolbe, H.J.; Thränhardt, A.; Weiser, G.; Thomas, P.; Koch, S.W. (Physica E: Low-dimensional Systems and Nanostructures)
A microscopic many-body theory for the linear and nonlinear optical properties of semiconductor superlattices subjected to electric fields is presented. The approach has been used for the analysis of various processes related to the Bloch-oscillation dynamics of carriers in static fields and for investigating dynamical localization induced by alternating fields. It is shown that the theory describes very well experimental field-modulated absorption spectra of a strongly coupled superlattice. Furthermore, characteristic signatures, such as negative absorption in the short-pulse optical response of superlattices subjected simultaneously to static and alternating electric fields are predicted.

Propagation of Coulomb-Correlated Electron-Hole Pairs in Semiconductors with Correlated and Anticorrelated Disorder - Meier, Torsten; Thomas, P.; Varga, I.; Lemm, T.; Golub, J.E.; Maschke, K.; Koch, S.W. (physica status solidi (b))
Local ultrafast optical excitation of electron–hole pairs in disordered semiconductors provides the possibility to observe experimentally interaction-assisted propagation of correlated quantum particles in a disordered environment. In addition to the interaction driven delocalization known for the conventional single-band TIP-(two-interacting-particles)-problem the semiconductor model has a richer variety of physical parameters that give rise to new features in the temporal dynamics. These include different masses, correlated versus anticorrelated disorder for the two particles, and dependence on spectral position of excitation pulse.

Investigation of Disordered Semiconductor Quantum Wells by Coherent Excitation Spectroscopy - Meier, Torsten; Euteneuer, A.; Finger, E.; Stolz, W.; Thomas, P.; Koch, S.W.; Hofmann, M.; Rühle, W.W.; Hey, R.; Ploog, K.H. (physica status solidi (a))
First, we study coupling of excitons in different quantum-well islands by coherent excitation spectroscopy and find that excitons in different islands are not coherently coupled. Second, we investigate exciton and biexciton binding energies in inhomogeneously broadened (GaIn)As/Ga(PAs) multi quantum wells. A strong increase of the 1s–2s-splitting with increasing exciton localization is found, whereas the biexciton binding energy shows a very weak decrease with increasing localization.

Disorder-induced Dephasing in Semiconductors - Meier, Torsten; Weiser, S.; Möbius, J.; Euteneuer, A.; Mayer, E.J.; Stolz, W.; Hofmann, M.; Rühle, W.W.; Thomas, P.; Koch, S.W. (Physical Review B)
Microscopic calculations including energetic disorder and Coulomb correlations up to third order in the laser field are performed. The resulting four-wave-mixing signals show polarization-dependent dephasing induced by diagonal disorder. The correct modeling of this disorder-induced dephasing requires the proper inclusion of Coulomb correlations. The theoretical results are in good qualitative agreement with measurements performed on a variety of quantum-well samples.

"Denn die Lehre feiert auch, und die Feier lehret" - Prospekt einer liturgischen Didaktik - Schroeter-Wittke, Harald

Ahnung von der Predigt. Konturen homiletischer Didaktik - Schroeter-Wittke, Harald

Unterhaltung - Praktisch-theologische Exkursionen zum homiletischen und kultirellen Bibelgebrauch im 19. und 20. Jahrhundert anhand der Figur Elia - Schroeter-Wittke, Harald

"Czy to ty jestes, Eliaszu?" Migawka z homiletycznego wykorzystania tekstów o Eliaszu poczawszy od 1945 roku - Schroeter-Wittke, Harald (Eliasz. Zeszyty ewangelickiego katechtey Nr. 2)

Prophetie - Politik - Pädagogik. Beobachtungen zu den Elias-Homilien des Darmstädter Hofpredigers Ferdinand Bender - Schroeter-Wittke, Harald (Jahrbuch der Hessischen Kirchengeschichtlichen Vereinigung)

Mendelssohns "Elias" - Ein Bibliodrama zwische Kirche und Konzertsaal - Schroeter-Wittke, Harald (Theophonie. Grenzgänge zwischen Musik und Theologie)

Theophonie. Grenzgänge zwischen Musik und Theologie. Anke Martiny zum 60. Geburtstag

Hast du Töne? Zum Umgang mit Musik - Schroeter-Wittke, Harald (Leistungskurs Religion. Vorlesungen zur Kunst der Religionspädagogik)

Das Evangelische Gottesdienstbuch und die liturgische Didaktik - Schroeter-Wittke, Harald (Deutsches Pfarrerblatt)

Praktische Theologie für kreative Gemeindearbeit. Ein Überblick zur gegenwärtigen deutschen Praktischen Theologie - Schroeter-Wittke, Harald; Hauschildt, Eberhard; Lee, Young-Mi

Kirchentag als Kunstereignis - Vision bislang nicht ausgeschöpfter Möglichkeiten - Schroeter-Wittke, Harald (Kirchentag aktuell März 2000)

Analysis of disorder-induced dephasing - Meier, Torsten; Weiser, S.; Möbius, J.; Euteneuer, A.; Mayer, E.J.; Stolz, W.; Hofmann, M.; Rühle, W.W.; Thomas, P.; Koch, S.W. (International Quantum Electronics Conference)
A number of experiments yielded a polarization-dependent decay of the time-integrated four-wavemixing (TI-FWM). Often, the TI-FWM decays more rapidly for linear perpendicular than for linear parallel polarized incident pulses. It was suspected that this difference in the decay times is related to the inhomogeneous linewidth of the exciton, i.e. to disorder [1], On the other hand, it was demonstrated in a large number of recent publications, that the understanding of polarization-dependent FWM and pump-probe experiments following excitonic excitation requires the treatment of Coulomb correlations beyond the Hartree-Fock level. For not too strong disorder, these correlations still remain important and influence the nonlinear optical response [2]. A meaningful analysis of disorder effects thus has to include correlations.

Influence of correlations on intensity dependent excitonic absorption changes - Meier, Torsten; Koch, S.W.; Brick, P.; Ell, C.; Khitrova, G.; Gibbs, H.M. (International Quantum Electronics Conference)
Polarization dependent excitonic absorption changes have been studied recently for excitation with weak pump pulses [1]. It was shown, that for both resonant and off-resonant excitation even in the low-intensity χ(3)-limit many-body Coulomb correlations strongly contribute the optical response [1]. Here we investigate, how the coherent pump-induced absorption changes vary with the pump intensity, by analyzing the next higher, i.e. the fifth-order contributions.

Coherent coupling in inhomogeneously broadened exciton ensembles - Meier, Torsten; Finger, E.; Kraft, S.; Euteneuer, A.; Hofmann, M.; Stolz, W.; Thomas, P.; Koch, S.W.; Rühle, W.W. (International Quantum Electronics Conference)
by inherent disorder effects. Inhomogeneous broadening is the most obvious consequence of disorder and an inhomogeneously broadened exciton line might be considered as a superposition of homogeneously broadened subensembles of excitons. However, a possible coherent coustructures and lead to effects like disorder induced dephasing [1].

Signatures of Correlations in Intensity Dependent Excitonic Absorption Changes - Meier, Torsten; Koch, S.W.; Brick, P.; Ell, C.; Khitrova, G.; Gibbs, H.M. (Physical Review B)
The intensity dependence of pump-induced excitonic absorption changes is studied in high-quality In0.04Ga0.96 As quantum wells for different detunings and polarization configurations. For resonant excitation with increasing pump intensity a saturation of both the exciton bleaching and the induced absorption due to two-exciton resonances is observed, whereas for pumping below the exciton a characteristic polarization dependence of higher-order contributions to the optical Stark effect is found. Microscopic calculations including Coulomb correlations show that the experimental observations can be described by the coherent dynamics of single- and two-exciton resonances up to fifth order in the optical field.

Strong coupling of heavy- and light-hole excitons induced by many-body correlations - Meier, Torsten; Koch, S.W.; Phillips, M.; Wang, H. (Physical Review B)
The differential absorption of a GaAs single quantum well is studied for resonant pumping at either the heavy- or light-hole exciton resonances using different polarization configurations. For all excitation conditions the observed spectra show bleaching of both excitons, revealing strong coupling between the heavy- and light-hole excitons. Microscopic calculations which include four-particle correlations representing the various two-exciton states qualitatively reproduce the experimental findings. A mixed heavy-hole–light-hole biexciton is also clearly identified as an induced resonance in a GaAs system.

Quantum theory of phonon-assisted exciton formation and luminescence in semiconductor quantum wells - Meier, Torsten; Thränhardt, A.; Kuckenberg, S.; Knorr, A.; Koch, S.W. (Physical Review B)
The phonon scattering assisted luminescence of semiconductor quantum well excitons after short pulse excitation is investigated. The presented analysis is based on the low-density limit of a set of equations for quantum correlation functions for electrons, phonons, and photons. The dynamics of the correlation functions describes the optical excitation and the decay of the coherent exciton polarization as well as the generation of an incoherent exciton occupation and its luminescence decay. Numerical solutions of the equations of motion demonstrate strong competition effects of the exciton-phonon and the exciton-photon interaction on a picosecond time scale and lead to a nonmonotonous temperature dependence of the time-resolved spontaneous emission. The angle resolved emission resembles the generation and decay dynamics of the exciton density for different in-plane momenta.

Correlation-induced resonances in differential absorption of semiconductors - Meier, Torsten; Phillips, M.; Wang, H.; Koch, S.W. (Quantum Electronics and Laser Science Conference (QELS 2000))
Extensive recent studies have provided valuable understanding on the role of correlations between excitons in optical interactions in semiconductors.

Coulomb Memory Effects and Higher-Order Coulomb Correlations in the Excitonic Optical Stark Effect - Meier, Torsten; Brick, P.; Ell, C.; Hübner, M.; Prineas, J.P.; Khitrova, G.; Gibbs, H.M.; Sieh, C.; Jahnke, F.; Knorr, A.; Koch, S.W. (physica status solidi (a))
Differential absorption spectra of high quality InGaAs quantum wells were measured by means of pump–probe spectroscopy as a function of pump–probe delay, for different polarizations of the pulses, and different spectral detunings of the pump beam with respect to the 1s heavy-hole exciton. A clear redshift of the heavy-hole resonance is observed for large detunings and opposite circularly polarized pulses. Microscopic calculations that include not only the Hartree-Fock contribution but also higher-order Coulomb correlations reproduce the experimental findings very well. It is shown that the redshift is caused by Coulomb memory effects and is further enhanced due to the presence of the bound biexciton.

Comparison of the differential absorption obtained within a few-level model and the microscopic density-matrix theory - Meier, Torsten; Reichelt, Matthias; Sieh, C.; Koch, S.W. (physica status solidi (b))
A phenomenological multi-exciton level scheme is used to calculate the excitonic differential absorption as measured in pump and probe experiments. Numerical results are compared to those obtained by a fully microscopic density-matrix theory. For resonant excitation, optimized parameters yield qualitative agreement, but the phenomenological approach soon reaches its limit for non-resonant pumping.

Current Echoes induced by Coherent Control - Meier, Torsten; Stippler, J.; Schlichenmaier, C.; Knorr, A.; Lindberg, M.; Thomas, P.; Koch, S.W. (physica status solidi (b))
A scheme to generate an experimentally measurable current echo is proposed where current pulses are induced by a sequence of phase coherent optical pulses. Based on microscopic calculations for a one-dimensional tight-bindig model of a disordered two-band semiconductor it is predicted that excitation sequences can be taylored such that after two induced time-delayed current pulses a current echo pulse results.

Microscopic Theory of Optical Dephasing in Semiconductors - Meier, Torsten; Koch, S.W.; Jahnke, F.; Thomas, P. (Applied Physics A)
Dephasing, i.e. the decay of the optical interband polarization in a semiconductor results from destructive interference effects between different microscopic contributions. For a system without any disorder it is shown that the many-body Coulomb correlations lead to excitation-induced dephasing which becomes increasingly important at elevated excitation levels. The effect of disorder-induced dephasing is analyzed for low excitation levels, where the combined influence of excitonic, biexcitonic, and disorder scattering contributions lead to a temporal decay of the four-wave-mixing signal.

Ikonographie der Nazizeit - Adelmann, Ralf; Keilbach, Judith (Über Bilder sprechen. Positionen und Perspektiven der Medienwissenschaft)